Large-scale compositional and electronic Inhomogeneities in CH3NH3PbI3 perovskites and their effect on device performance - Sun, Qing; Faßl, Paul; Vaynzof, Yana (ACS applied energy materials, 2018)
Photovoltaic devices based on lead halide perovskite materials are under extensive investigation due to their remarkably high efficiencies. However, it has become evident that the photovoltaic performance of these devices shows wide distributions, even across individual perovskite samples, resulting in the practice of presenting performance histograms, rather than single values. We demonstrate that these variations in performance are related to the large-scale compositional and electronic inhomogeneities of perovskite films, which we characterize using X-ray and ultraviolet photoemission spectroscopy mapping. These inhomogeneities are observed for three different fabrication methods for the perovskite layers, and while they are unaltered by storage in nitrogen and dry air, long-term exposure to vacuum increases the homogeneity of the surface structure. We demonstrate that perovskite films with a nonuniform surface structure result in broadly varying photovoltaic performance despite seemingly similar bulk properties such as absorption and microstructure.
Im Titel ist „3“ jeweils tiefgestellt
Gesehen am 25.04.2019